Linking supply chain social capital factors, supply chain integration strategy and operational performance in the Malaysian food processing industry / Zurita Mohd Saleh - Mohd Saleh, Zurita (Institute of Graduate Studies, UiTM, 2017)
The food processing industry has become a significant contributor to Malaysia’s socio-economy and is also an important source of employment. However, lately, this industry has been experiencing problems in terms of its fragmented supply chain system, lack of latest technology adoption, substandard grades of raw materials and low product innovation. Furthermore, this industry is often associated with poor understanding and execution of best business practices. The current business environment has witnessed increased competition from foreign food companies having the same entry opportunities in the local market whilst many of the Malaysian food processing companies find it difficult to penetrate overseas market. To a large extent this is because of aggressive competition from the counterparts in Thailand, Indonesia and China, who have already established their presence globally and are more receptive to market changes. Existing studies have established that supply chain is the key towards competitive ability. In view of this, there is a need to investigate the supply chain integration strategy (SC integration strategy) between the food manufacturers and their supply chain partners both internally and externally. This study focuses on how to improve the operational performance of the food processing industry. It analyses the integration strategy between food manufacturers and its supply chain partners to allow for greater understanding in the field of supply chain management (SCM). Drawing upon the Supply Chain Management (SCM) perspectives and Social Capital Theory, this study evaluates the relationships between critical constructs; Supply chain (SC) structural, Supply chain (SC) relational, Supply chain (SC) cognitive, Supply chain (SC) integration strategy and operational performance…